At-Tawasul al-Fikri baina al-Hadarah al-Islamiyah wa al-Hadarah al-Igriqiyyah - Isa Abdullah Ali (IAIN Surakarta, 2017)
This article aims to describe how early Islamic civilization was formed, which later became the foundation for later Islamic civilization. This paper with a historical approach tries to explain about the intellectual communication between the early Islamic civilization with the Greek civilization. This paper found that communication between Islamic civilization with Greek civilization started from the interaction process of Islamic scholars with Greek works through the process of massive translation during the Caliph Al-Mamun. The results of this translation have implications for the philosophy and theology of Islam proposed by early Islamic thinkers and philosophers. Although the philosophical and theological thinking they constructed was a Hellenistic, they blended on the principles of Islamic teachings, making it a distinctive philosophy and theology of Islam. From this was born Islamic civilization built on the foundation of faith and science in a balanced way, which is different from the Greek civilization is not based on faith. Intellectual communication between Islamic civilization with this Greek civilization which later gave birth to the European Renaissance.